2x = 17 then x = 8.5 2x+1=7 then x = 3 2x - 1 = 7 then x = 4 which is your problem
2x+17=6x-23 23+17=6x-2x 40=4x x=40 / 4 therefore x=10
6x-8+2x-5 = 7-2x 6x+2x+2x = 7+8+5 10x = 20 x = 20/10 x = 2
The number is -14/23 or -0.6087. Let x = the number Equation: 1/2 * x = 12 * x + 7 multiplying the equation by 2 2(1/2x) = (12x + 7)2 x = 24x + 14 x - 24x = 14 -23x = 14 x = -14/23 or -0.6087 check: 1/2 * x = 12 * x + 7 1/2 (-14/23) = 12 (-14/23) + 7 -14/46 = -168/23 + 161/23 -7/23 = -7/23
(2x - 7)(x + 1)
2x + 7 + 2x = 23 4x + 7 = 23 4x = 16 x = 16/4 x = 4
2x + 7 = 30 - 7 - 7 2x = 23 x = 23/2 x = 11.5
x+7 = 2x 2x = x+7 2x-x = 7 x = 7
f(x)= (x-7) /(-2x+7)(2x+5) set -2x+7=0 -2x=-7 x=7/2 set 2x+5=0 2x=-5 x=-5/2 x=7/2 and x=-5/2 are vertical asymptotes.
2x = 17 then x = 8.5 2x+1=7 then x = 3 2x - 1 = 7 then x = 4 which is your problem
3x - 12 = -2x + 235x = 35 so x = 7
-7 +2x = x + 8 2x - x = 7 + 8 x = 15
x = 23
f(x) = 2x + 8 f(x) = -7 → 2x + 8 = -7 → 2x = -15 → x = -7½ = -7.5
56 = 2 x 2x 2 x 7 56 = 23 x 7
10 + 2(x - 1) + 7 x 3x + 1 =10 + 2x - 2 + (7 x 3x) + 1 =10 + 2x - 2 + 21x + 1 =2x + 21x + 10 - 2 + 1 =23x + 9
6x-7 = 4x+23 (take the x terms on one side and the number terms on the other) 6x -4x = 23 + 7 therefore 2x = 30 x=30/2 x=15